3D-Printed Hand Controlled by Arm Gestures to Verify the Robustness and Reliability of a Low Cost Surface Electromyography System - Manlapaz, Ma. Erika (Archīum Ateneo, 2015)
The study focuses on the development of a low-cost surface electromyography and 3D-printed hand gesture-recognition system. The complete system captures four (4) channels of EMG data through sEMG amplifier circuits interfaced to an Arduino prototyping board. This data is sent to a workstation wherein the graphical user interface shows the pre-processed signal. The gestures are used as control for the movements of the 3D-printed arm.